Health care network (dis)articulation in late and moderate prematurity - Leonardo Bigolin Jantsch; Thauana Ferreira Alves; Andrea Moreira Arrué; Beatriz Rosana Gonçalves de Oliveira Toso; Eliane Tatsch Neves (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze the Health Care Network (dis)articulation of late and moderate premature infants in the first year of life. Method: a qualitative study with semi-structured interview, which addressed the care network constitution in a municipality in southern Brazil. Fifteen mothers of infants participated. Thematic content analysis and flowchart were used to describe networks and services. Results: first contact in Primary Health Care is a decisive factor for the recognition and articulation of neonates/infants in the network and enables resolution, especially in childcare demands. Secondary and hospital care services support isolated acute events or chronic conditions, without articulation between levels of care and in a uniprofessional way. Final considerations: attention to health conditions is organized and structured in a uniprofessional, fragmented and disjointed way, which makes it impossible to form a Health Care Network premature infants' perspective.